Energy conversion device based on flexible electromagnetic wave absorbing material and preparation method thereof
By using energy conversion devices of flexible electromagnetic wave absorbing materials in wearable devices, using wave absorption and heat generation and electricity generation methods, the stability and sustainability problems of traditional power supply methods are solved, and efficient power supply and performance improvement are achieved.
Patent Information
- Application Number
- CN202411941082.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The prior art is difficult to achieve stable and continuous power supply in wearable devices, and traditional battery power supply has limitations on performance improvement and application scenario extension.
The energy conversion device based on flexible electromagnetic wave absorbing materials is adopted to achieve efficient collection and conversion of electromagnetic wave energy by absorbing waves and generating heat and then generating electricity. The device is composited by magnetic nanoparticles @nitrogen-doped carbon with polymer, combined with a multi-layer structure of thermally conductive silicon grease and copper foil, enhancing electromagnetic wave attenuation and thermal energy conduction.
It has achieved widespread application in wearable devices, provided an effective solution to power passive wearable devices using waste electromagnetic radiation, and solved the stability and sustainability of traditional power supply methods.
Smart Images

Figure CN119768020A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an energy conversion device based on a flexible electromagnetic wave absorbing material and a preparation method thereof, belonging to the technical field of composite functional materials. Background Art
[0002] With the widespread application of new generation information and communication technology and various electronic products, electromagnetic pollution is becoming increasingly serious. Electromagnetic radiation not only interferes with the normal operation of electronic components, but also harms human health. Electromagnetic wave absorbing materials can convert electromagnetic wave energy into heat energy and dissipate it based on multiple mechanisms of magnetic loss and electrical loss, becoming a key strategy to solve the problem of electromagnetic radiation. At the same time, with the rapid development of electronic technology, the field of wearable electronic equipment has made significant progress, and the integration of various electronic products has been increasing, showing a trend towards high efficiency, miniaturization and intelligence. However, the integration of various electronic components not only brings about the problems of electromagnetic interference and radiation, but also requires the development of light, thin and flexible sustainable energy supply devices. At present, wearable devices are generally powered by batteries, which seriously restricts their further development and breakthroughs in performance improvement, function expansion and application scenario extension, and has become a key problem to be solved in this field.
[0003] In the prior art, in response to the energy supply problem of passive wearable sensors, many studies are devoted to the effective utilization of various types of energy in the environment, such as collecting kinetic energy, solar energy and thermal energy, and further converting them into other energy forms that can be reused. CN202111122744.7, CN202211042071.9, CN202310972616.4 and CN202210548446.2 proposed the use of friction power generation to continuously power passive devices that monitor human motion status or health indicators. However, this energy utilization conversion device based on mechanical friction has a complicated internal structure and a relatively narrow application scenario, making it difficult to provide energy for passive sensors in a wider range of fields. CN202310583675.2, CN202110775134.0, and CN201910310265.4 focus on converting solar energy into electrical energy and implementing charging control operations for related devices. However, this energy supply method is significantly restricted by environmental factors, and it is difficult to ensure a stable and continuous power supply during actual use. CN202310969955.7, CN202310090664.0 and ZL201510328818.0 proposed boosting energy storage after passive RF signal recognition, and applied it to positioning services or temperature detection. The defect is that it can only recognize low-frequency signals, and adopts a contact response mode for temperature detection, which limits the detection range. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides an energy conversion device based on flexible electromagnetic wave absorbing materials and a preparation method thereof. It adopts the method of absorbing waves to generate heat and then generating electricity, which can achieve efficient collection and conversion of electromagnetic wave energy and realize wide application in wearable equipment.
[0005] To achieve the above object, the present invention proposes a method for preparing an energy conversion device based on a flexible electromagnetic wave absorbing material, the method comprising the following steps:
[0006] 1) dissolving the ionic compound in dilute hydrochloric acid, and adding Na3C6H5O7·2H2O and polyvinyl pyrrolidone to form solution A, dissolving two or more of K3[Fe(CN)6], K4[Fe(CN)6]·3H2O, and K3[Co(CN)6] in dilute hydrochloric acid to form solution B, mixing solution A and solution B, heating in a water bath after fully mixing, and post-treating to obtain a PBAs precursor;
[0007] 2) heat-treating the PBAs precursor to obtain magnetic nanoparticles@nitrogen-doped carbon;
[0008] 3) adding the magnetic nanoparticles @ nitrogen-doped carbon into a high molecular polymer solution, and then pouring the mixed solution into a mold to obtain a flexible composite sheet, which is also a flexible electromagnetic wave absorbing material;
[0009] 4) The flexible composite sheet is used as the top material, a layer of the first thermal grease is coated on the bottom, a copper foil is then attached to the lower surface of the thermal grease, a layer of the second thermal grease is filled under the copper foil, and a semiconductor temperature difference power generation sheet is arranged under the second thermal grease to obtain the energy conversion device based on the flexible electromagnetic wave absorbing material.
[0010] According to a preferred embodiment of the present invention, in step 1), the ionic compound is Fe 3+ 、Co 2+ 、Ni 2+ Chloride compounds, Fe 3+ 、Co 2+ 、Ni 2+ Nitrate compounds or Fe 3+ 、Co 2+ 、Ni 2+ The ionic compound contains at least two metal elements. Preferably, the concentration of dilute hydrochloric acid in solution A and solution B is 0.1-1 mol / L.
[0011] According to a preferred embodiment of the present invention, in step 1), the total concentration of ionic compounds in solution A is 0.01-0.2 mol / L, and the total concentration of K3[Fe(CN)6], K4[Fe(CN)6]·3H2O, and K3[Co(CN)6] in solution B is 0.01-0.2 mol / L. Preferably, the volume ratio of solution A to solution B is 1:1. Preferably, the concentration of Na3C6H5O7·2H2O in solution A is 0.02-0.5 g / mL, and the concentration of polyvinyl pyrrolidone in solution A is 0.02-0.5 g / mL.
[0012] According to a preferred embodiment of the present invention, in step 1), the temperature range of the water bath heating is 80-100°C, the reaction time is 6-8 hours, and the post-treatment is: cooling after the reaction is completed, collecting the precipitate by centrifugation, washing with deionized water and anhydrous ethanol in sequence, and drying in a vacuum oven to obtain a PBAs precursor.
[0013] According to a preferred embodiment of the present invention, the magnetic nanoparticles@nitrogen-doped carbon prepared in step 2) are Fe 100-a Co a , Fe 100-b Ni b or Fe 100-c-d Co c Ni d One of the following, where 10≤a<50, 10≤b<50, 10≤c≤30, 10≤d≤20.
[0014] According to a preferred embodiment of the present invention, the temperature of the heat treatment in step 2) is 600-800°C, and the heat treatment time is 2-3 hours; the heat treatment is carried out under a certain atmosphere, and the atmosphere is argon, nitrogen, or a mixed gas of argon and hydrogen. Preferably, the volume ratio of hydrogen in the mixed gas is 10%.
[0015] According to a preferred embodiment of the present invention, the high molecular polymer is one of polyurethane, polyvinyl alcohol, polydimethylsiloxane or polyvinyl butyral; the mass ratio of the magnetic nanoparticles @ nitrogen-doped carbon to the high molecular polymer is (1:9) to (2:3).
[0016] According to a preferred embodiment of the present invention, in step 3), the magnetic nanoparticles @ nitrogen-doped carbon are mixed with a high molecular polymer solution, ultrasonic treatment is used to make the sample evenly dispersed, and then it is quickly poured into a mold. After the mold is filled by mechanical oscillation, it is placed in a vacuum oven for evacuation and degassing and drying to obtain a flexible composite sheet.
[0017] According to a preferred embodiment of the present invention, the flexible composite sheet is composed of magnetic nanoparticles@nitrogen-doped carbon / high molecular polymer, and the mass fraction of magnetic nanoparticles@nitrogen-doped carbon in the flexible composite sheet is 10-40 wt.%.
[0018] The present invention also provides an energy conversion device based on a flexible electromagnetic wave absorbing material prepared by the method, which is an electromagnetic energy-thermal energy-electrical energy conversion device.
[0019] The present invention is based on PBAs derivatives and designs an electromagnetic wave energy conversion device with wide frequency band, light weight and good flexibility. It is compatible with wearable devices and can be converted into usable electrical energy through a thermoelectric module. By optimizing the ratio of magnetic elements in PBAs derivatives, the regulation of magnetic loss can be achieved, and the magnetic nanoparticles @ nitrogen-doped carbon obtained after heat treatment can effectively optimize impedance matching. Constructing a multilayer structure with absorbing sheets, thermal conductive silicone grease and copper foil can not only achieve multiple reflections and scattering of electromagnetic waves, but also enhance the heat energy conduction path, and directly introduce the converted heat energy into the semiconductor thermoelectric power generation sheet and convert it into electrical energy. The energy conversion device based on flexible electromagnetic wave absorbing materials provides an effective solution for utilizing waste and harmful electromagnetic radiation to power passive wearable devices.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. Fe involved in the present invention 3+ 、Co 2+ 、Ni 2+ Chloride compounds, Fe 3+ 、Co 2+ 、Ni 2+ Nitrate compounds or Fe 3+ 、Co 2+ 、Ni 2+ The magnetic loss contributed by the magnetic properties of two or more metal elements in the sulfate compounds plays an important role. By adjusting the content of metal elements in the above salt compounds and PBAs, the composition ratio can be adjusted to change the magnetic properties of magnetic nanoparticles, and then the wave absorption performance can be controlled.
[0022] 2. The flexible electromagnetic wave absorbing material of the present invention combines dielectric materials with magnetic materials to improve the impedance matching of the absorbing material. The cross-linking of the three-dimensional spherical carbon network can accelerate the jumping or migration of electrons in the material and convert microwave energy into thermal energy by colliding with the lattice. In addition, nitrogen and oxygen atoms are doped into the carbon skeleton to form many defect sites and oxygen-containing functional groups, providing a large amount of dipole loss and defect loss. In addition, the heterogeneous interface between the magnetic nanoparticles and the carbon matrix provides interface polarization. The magnetic nanoparticles provide magnetic losses mainly from eddy current effects, natural resonances, and exchange resonances. The synergistic effect of multiple effects and loss mechanisms can significantly enhance the attenuation of electromagnetic waves.
[0023] 3. The present invention adopts the prepared flexible composite sheet magnetic nanoparticles @ nitrogen-doped carbon / high molecular polymer as the top layer material, and constructs a thermal grease-copper foil-thermal grease multilayer structure, which not only realizes the effective loss of electromagnetic waves, but also increases the electromagnetic wave propagation path. Multiple reflections and scattering enhance the electromagnetic wave attenuation, while better conducting heat for subsequent utilization. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a physical picture of the flexible composite sheet magnetic nanoparticles @ nitrogen-doped carbon / high molecular polymer according to an embodiment of the present invention;
[0025] Figure 2 is a schematic diagram of an energy conversion device based on a flexible electromagnetic wave absorbing material according to an embodiment of the present invention;
[0026] Figure 3 It is a schematic diagram of the connection and application of the electromagnetic wave energy-heat energy-electric energy conversion device of the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described and illustrated below in conjunction with specific embodiments. The embodiments are merely exemplary of the present disclosure and do not define the scope of limitation. The technical features of each embodiment of the present invention may be combined accordingly without conflicting with each other.
[0028] Example 1
[0029] 1) Synthesis of PBAs precursors:
[0030] According to the molar ratio of Fe:Co=70:30, weigh 0.77363g of FeCl3·6H2O compound and 0.87309g of Co(NO3)2·6H2O compound and dissolve them in a dilute hydrochloric acid solution with a concentration of 0.1mol / L, then add 1.821g of Na3C6H5O7·2H2O and 2g of PVP in sequence, stir well to form solution A, then weigh 0.65800g of K3[Fe(CN)6] and 0.90308g of K4[Fe(CN)6]·3H2O and add them in a dilute hydrochloric acid solution with a concentration of 0.1mol / L, stir well to obtain solution B. Slowly add solution B dropwise to the stirred solution A, stir well to mix, seal and place in a water bath at a temperature of 80°C, and react for 8 hours. After cooling, collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol in sequence, and dry in a vacuum oven;
[0031] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0032] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 600° C. in an atmosphere of inert gas Ar for 3 hours, and then cooled to room temperature to obtain a final product;
[0033] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane):
[0034] The sample collected in step 2) was added to the polyurethane solution to prepare a composite sheet. 3.072 g of polyurethane was weighed and the solution was prepared. The polyurethane was completely dissolved by ultrasound. Then 0.768 g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet was 20 wt.%) was weighed. The sample was evenly dispersed by ultrasound treatment. Then, it was quickly poured into a customized mold. After mechanical oscillation to fill the mold, it was placed in a vacuum oven to evacuate and remove bubbles. Then, it was dried to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane). Figure 1 As shown;
[0035] 4) Construct electromagnetic energy-thermal energy-electrical energy conversion device:
[0036] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane) prepared in step 3) is used as the top material, a layer of thermal grease is coated on the bottom, then a copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil, and a semiconductor temperature difference power generation sheet is arranged under the thermal grease filled later, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained, such as Figure 2 As shown, in order to facilitate heat dissipation, a water cooling device is arranged at the bottom of the electromagnetic wave energy-heat energy-electric energy conversion device, and cooling water is used to cool the semiconductor temperature difference power generation chip.
[0037] The obtained magnetic nanoparticles@nitrogen-doped carbon sample was tested for its microwave absorption performance using a coaxial method. The results are shown in Table 1. Figure 3 The electromagnetic wave energy-heat energy-electric energy conversion device of the present invention is shown in the following figure. Figure 3 The performance test was carried out according to the schematic connection relationship. Table 2 shows the electrical output characteristics of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0038] Table 1 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0039]
[0040] Table 2 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0041]
[0042] Example 2
[0043] 1) Synthesis of PBAs precursors:
[0044] According to the molar ratio of Fe:Co=90:10, weigh 1.92309g of Fe(NO3)3·9H2O compound and 0.23800g of Co(Cl)2·6H2O compound and dissolve them in a dilute hydrochloric acid solution with a concentration of 0.3mol / L, then add 1.910g of Na3C6H5O7·2H2O and 2.5g of PVP in sequence, stir well to form solution A, then weigh 0.22043g of K3[Fe(CN)6] and 1.50654g of K4[Fe(CN)6]·3H2O and add them in a dilute hydrochloric acid solution with a concentration of 0.3mol / L in sequence, stir well to obtain solution B. Slowly add solution B dropwise to the stirred solution A, stir well to mix, seal and place in a water bath at a temperature of 85°C, and react for 8 hours. After cooling, collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol in sequence, and dry in a vacuum oven;
[0045] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0046] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 650° C. in an atmosphere of inert gas N2 for 3 hours, and then cooled to room temperature to obtain a final product;
[0047] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl alcohol):
[0048] The sample collected in step 2) is added to the polyvinyl alcohol solution to prepare a composite sheet. Weigh 3.456g of polyvinyl alcohol to prepare the solution, completely dissolve the polyvinyl alcohol by ultrasound, and then weigh 0.384g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 10wt.%), use ultrasonic treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl alcohol);
[0049] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0050] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl alcohol) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0051] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 3. Table 4 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0052] Table 3 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0053]
[0054] Table 4 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0055]
[0056] Example 3
[0057] 1) Synthesis of PBAs precursors:
[0058] According to the molar ratio of Fe:Co=55:45, weigh 0.38682g of FeCl3·6H2O compound and 1.30964g of Co(NO3)2·6H2O compound and dissolve them in a 0.5mol / L dilute hydrochloric acid solution, then add 1.700g of Na3C6H5O7·2H2O and 1.5g of PVP in sequence, stir well to form solution A, then weigh 0.98700g of K3[Fe(CN)6] and 0.45154g of K4[Fe(CN)6]·3H2O and add them in a 0.5mol / L dilute hydrochloric acid solution in sequence, stir well to obtain solution B. Slowly add solution B dropwise to the stirred solution A, stir well to mix, seal and place in a water bath at 90°C, and react for 7 hours. After cooling, collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol in sequence, and dry in a vacuum oven;
[0059] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0060] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 700° C. in an atmosphere of a mixed gas Ar / H2 (10 vol% H2) for 2.5 hours, and then cooled to room temperature to obtain a final product;
[0061] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polydimethylsiloxane):
[0062] Add the sample collected in step 2) to the polydimethylsiloxane solution to prepare a composite sheet. Weigh 2.688g of polydimethylsiloxane to prepare the solution, completely dissolve the polydimethylsiloxane by ultrasound, and then weigh 1.152g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 30wt.%), use ultrasonic treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polydimethylsiloxane);
[0063] 4) Construct electromagnetic energy-thermal energy-electrical energy conversion device:
[0064] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polydimethylsiloxane) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0065] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 5. Table 6 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0066] Table 5 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0067]
[0068] Table 6 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0069]
[0070] Example 4
[0071] 1) Synthesis of PBAs precursors:
[0072] According to the molar ratio of Fe:Ni=75:25, weigh 1.34535g of Fe(NO3)3·9H2O compound and 0.65713g of Ni(SO4)2·6H2O compound and dissolve them in a dilute hydrochloric acid solution with a concentration of 0.7mol / L, then add 1.865g of Na3C6H5O7·2H2O and 2g of PVP in sequence, stir well to form solution A, then weigh 0.54943g of K3[Fe(CN)6] and 1.05500g of K4[Fe(CN)6]·3H2O and add them in a dilute hydrochloric acid solution with a concentration of 0.7mol / L in sequence, stir well to obtain solution B. Slowly add solution B dropwise to the stirred solution A, stir well to mix, seal and place in a water bath at a temperature of 80°C, and react for 6 hours. After cooling, collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol in sequence, and dry in a vacuum oven;
[0073] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0074] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 700° C. in an atmosphere of inert gas Ar for 2 hours, and then cooled to room temperature to obtain a final product;
[0075] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl butyral):
[0076] The sample collected in step 2) is added to the polyvinyl butyral solution to prepare a composite sheet. Weigh 3.072g of polyvinyl butyral to prepare the solution, completely dissolve the polyvinyl butyral by ultrasound, and then weigh 0.768g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 20wt.%), use ultrasonic treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl butyral);
[0077] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0078] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl butyral) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0079] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 7. Table 8 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0080] Table 7 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0081]
[0082] Table 8 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0083]
[0084] Example 5
[0085] 1) Synthesis of PBAs precursors:
[0086] According to the molar ratio of Fe:Ni=90:10, weigh 1.28758g of FeCl3·6H2O compound and 0.23769g of Ni(Cl)2·6H2O compound and dissolve them in a dilute hydrochloric acid solution with a concentration of 0.9mol / L, then add 2g of Na3C6H5O7·2H2O and 3g of PVP in sequence, stir well to form solution A, then weigh 0.22043g of K3[Fe(CN)6] and 1.50654g of K4[Fe(CN)6]·3H2O and add them in a dilute hydrochloric acid solution with a concentration of 0.9mol / L in sequence, stir well to obtain solution B. Slowly add solution B dropwise to the stirred solution A, stir well to mix, seal and place in a water bath at a temperature of 100°C, and react for 6 hours. After cooling, collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol in sequence, and dry in a vacuum oven;
[0087] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0088] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 800° C. in an atmosphere of inert gas N2 for 2.5 hours, and then cooled to room temperature to obtain a final product;
[0089] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane):
[0090] The sample collected in step 2) is added to the polyurethane solution to prepare a composite sheet. Weigh 3.456g of polyurethane to prepare the solution, completely dissolve the polyurethane by ultrasound, and then weigh 0.384g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 10wt.%), use ultrasound treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane);
[0091] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0092] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0093] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 9. Table 10 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0094] Table 9 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0095]
[0096] Table 10 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0097]
[0098] Example 6
[0099] 1) Synthesis of PBAs precursors:
[0100] According to the molar ratio of Fe:Ni=52:48, weigh 0.30837g of FeCl3·6H2O compound and 1.14091g of Ni(Cl)2·6H2O compound and dissolve them in a 1.0mol / L dilute hydrochloric acid solution, then add 1.764g of Na3C6H5O7·2H2O and 1g of PVP in sequence, stir well to form solution A, then weigh 1.05280g of K3[Fe(CN)6] and 0.36292g of K4[Fe(CN)6]·3H2O and add them in sequence to a 1.0mol / L dilute hydrochloric acid solution, stir well to obtain solution B. Slowly add solution B dropwise to the stirred solution A, stir well to mix, seal and place in a water bath at 85°C, and react for 7 hours. After cooling, collect the precipitate by centrifugation, wash with deionized water and anhydrous ethanol in sequence, and dry in a vacuum oven;
[0101] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0102] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 650° C. in an atmosphere of a mixed gas Ar / H2 (10 vol% H2) for 3 hours, and cooled to room temperature to obtain a final product;
[0103] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl alcohol):
[0104] The sample collected in step 2) is added to the polyvinyl alcohol solution to prepare a composite sheet. Weigh 2.688g of polyvinyl alcohol to prepare the solution, completely dissolve the polyvinyl alcohol by ultrasound, and then weigh 1.152g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 30wt.%), use ultrasonic treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl alcohol);
[0105] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0106] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyvinyl alcohol) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0107] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 11. Table 12 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0108] Table 11 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0109]
[0110] Table 12 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0111]
[0112] Example 7
[0113] 1) Synthesis of PBAs precursors:
[0114] According to the molar ratio of Fe:Co:Ni=60:20:20, 0.51395g of FeCl3·6H2O compound, 0.47600g of Co(Cl)2·6H2O compound and 0.47538g of Ni(Cl)2·6H2O compound were weighed and dissolved in a 0.5mol / L dilute hydrochloric acid solution, and then 2g of Na3C6H5O7·2H2O and 2g of PVP were added in sequence, and stirred well to form solution A, and then 0.87843g of K3[Fe(CN)6] and 0.60346g of K4[Fe(CN)6]·3H2O were weighed and added in sequence to a 0.5mol / L dilute hydrochloric acid solution, and stirred well to obtain solution B. Solution B was slowly added dropwise to the stirred solution A, and after being stirred well, the mixture was sealed and placed in a water bath at a temperature of 80°C for 8 hours. After cooling, the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol in sequence, and dried in a vacuum oven;
[0115] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0116] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 600° C. in an atmosphere of inert gas Ar for 3 hours, and then cooled to room temperature to obtain a final product;
[0117] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane):
[0118] The sample collected in step 2) is added to the polyurethane solution to prepare a composite sheet. Weigh 3.072g of polyurethane to prepare the solution, completely dissolve the polyurethane by ultrasound, and then weigh 0.768g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 20wt.%), use ultrasound treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane);
[0119] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0120] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0121] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 13. Table 14 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0122] Table 13 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0123]
[0124] Table 14 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0125]
[0126] Example 8
[0127] 1) Synthesis of PBAs precursors:
[0128] According to the molar ratio of Fe:Co:Ni=70:20:10, 1.15547g of Fe(NO3)3·9H2O compound, 0.58206g of Co(NO3)2·6H2O compound and 0.26285g of Ni(SO4)2·6H2O compound were weighed and dissolved in a 0.1mol / L dilute hydrochloric acid solution, and then 2g of Na3C6H5O7·2H2O and 1.5g of PVP were added in sequence, and stirred well to form solution A, and then 0.65800g of K3[Fe(CN)6] and 0.90308g of K4[Fe(CN)6]·3H2O were weighed and added in sequence to a 0.1mol / L dilute hydrochloric acid solution, and stirred well to obtain solution B. Solution B was slowly added dropwise to the stirred solution A, and after being stirred well, the mixture was sealed and placed in a water bath at a temperature of 90°C for 7 hours. After cooling, the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol in sequence, and dried in a vacuum oven;
[0129] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0130] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 700° C. in an atmosphere of inert gas N2 for 2.5 hours, and then cooled to room temperature to obtain a final product;
[0131] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane):
[0132] The sample collected in step 2) is added to the polyurethane solution to prepare a composite sheet. Weigh 2.688g of polyurethane to prepare the solution, completely dissolve the polyurethane by ultrasound, and then weigh 1.152g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 30wt.%), use ultrasound treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane);
[0133] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0134] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0135] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 15. Table 16 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0136] Table 15 Microwave absorption properties of magnetic nanoparticles@nitrogen-doped carbon
[0137]
[0138] Table 16 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0139]
[0140] Example 9
[0141] 1) Synthesis of PBAs precursors:
[0142] According to the molar ratio of Fe:Co:Ni=70:10:20, 1.15547g of Fe(NO3)3·9H2O compound, 0.29103g of Co(NO3)2·6H2O compound and 0.52570g of Ni(SO4)2·6H2O compound were weighed and dissolved in a 1mol / L dilute hydrochloric acid solution, and then 2g of Na3C6H5O7·2H2O and 2.5g of PVP were added in sequence, and stirred thoroughly to form solution A, and then 0.65800g of K3[Fe(CN)6] and 0.90308g of K4[Fe(CN)6]·3H2O were weighed and added in sequence to a 1mol / L dilute hydrochloric acid solution, and stirred thoroughly to obtain solution B. Solution B was slowly added dropwise to the stirred solution A, and after being stirred thoroughly, it was sealed and placed in a water bath at a temperature of 100°C for 6 hours. After cooling, the precipitate was collected by centrifugation, washed with deionized water and anhydrous ethanol in sequence, and dried in a vacuum oven;
[0143] 2) Preparation of magnetic nanoparticles @ nitrogen-doped carbon:
[0144] The sample obtained in step 1) is placed in a tube furnace for heat treatment at a temperature of 800° C. in an atmosphere of a mixed gas Ar / H2 (10 vol% H2) for 2 hours, and then cooled to room temperature to obtain a final product;
[0145] 3) Casting flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane):
[0146] The sample collected in step 2) is added to the polyurethane solution to prepare a composite sheet. Weigh 2.304g of polyurethane to prepare the solution, completely dissolve the polyurethane by ultrasound, and then weigh 1.536g of magnetic nanoparticles @ nitrogen-doped carbon (the mass fraction of magnetic nanoparticles @ nitrogen-doped carbon in the final flexible composite sheet is 40wt.%), use ultrasound treatment to evenly disperse the sample, and then quickly pour it into a customized mold, mechanically oscillate the filled mold, put it into a vacuum oven to evacuate and remove bubbles, and then dry it to obtain a flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane);
[0147] 4) Constructing electromagnetic wave energy-heat energy-electric energy conversion device:
[0148] The flexible composite sheet (magnetic nanoparticles @ nitrogen-doped carbon / polyurethane) prepared in step 3) is used as the top material, and a layer of thermal grease is coated on the bottom. Then, a piece of copper foil is attached to the lower surface of the thermal grease, and then a layer of thermal grease is filled under the copper foil. A semiconductor temperature difference power generation sheet is arranged under the thermal grease, and finally an electromagnetic wave energy-heat energy-electric energy conversion device is obtained.
[0149] The obtained magnetic nanoparticles @ nitrogen-doped carbon sample was tested for wave absorption performance by the coaxial method, and the results are shown in Table 17. Table 18 shows the output of the open circuit voltage (mV) versus frequency of the corresponding electromagnetic wave energy-heat energy-electric energy conversion device constructed under the electromagnetic wave input power of 9W and the irradiation time of 300s.
[0150] Table 17 Microwave absorption properties of magnetic nanoparticles @ nitrogen-doped carbon
[0151]
[0152] Table 18 Open circuit voltage output of electromagnetic wave energy-heat energy-electric energy conversion device
[0153]
[0154] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing an energy conversion device based on a flexible electromagnetic wave absorbing material, characterized in that: The steps include: 1) dissolving the ionic compound in dilute hydrochloric acid, and adding Na3C6H5O7·2H2O and polyvinyl pyrrolidone to form solution A, dissolving two or more of K3[Fe(CN)6], K4[Fe(CN)6]·3H2O, and K3[Co(CN)6] in dilute hydrochloric acid to form solution B, mixing solution A and solution B, heating in a water bath after fully mixing, and post-treating to obtain a PBAs precursor; 2) heat-treating the PBAs precursor to obtain magnetic nanoparticles@nitrogen-doped carbon; 3) adding the magnetic nanoparticles@nitrogen-doped carbon into a high molecular polymer solution, and then pouring the mixed solution into a mold to obtain a flexible composite sheet; 4) The flexible composite sheet is used as the top material, a layer of the first thermal grease is coated on the bottom, a copper foil is then attached to the lower surface of the thermal grease, a layer of the second thermal grease is filled under the copper foil, and a semiconductor temperature difference power generation sheet is arranged under the second thermal grease to obtain the energy conversion device based on the flexible electromagnetic wave absorbing material.
2. The preparation method according to claim 1, characterized in that: In step 1), the ionic compound is Fe 3+ 、Co 2 + 、Ni 2+ Chloride compounds, Fe 3+ 、Co 2+ 、Ni 2+ Nitrate compounds or Fe 3+ 、Co 2+ 、Ni 2+ The sulfate compound, and the ionic compound contains at least two metal elements; the concentration of dilute hydrochloric acid in solution A and solution B is 0.1-1 mol / L.
3. The preparation method according to claim 1, characterized in that: In step 1), the total concentration of ionic compounds in solution A is 0.01-0.2 mol / L, the total concentration of K3[Fe(CN)6], K4[Fe(CN)6]·3H2O, and K3[Co(CN)6] in solution B is 0.01-0.2 mol / L; the volume ratio of solution A to solution B is 1:1; the concentration of Na3C6H5O7·2H2O in solution A is 0.02-0.5 g / mL, and the concentration of polyvinyl pyrrolidone in solution A is 0.02-0.5 g / mL.
4. The preparation method according to claim 1, characterized in that: In step 1), the temperature range of the water bath heating is 80-100° C., the reaction time is 6-8 hours, and the post-treatment is as follows: cooling after the reaction is completed, collecting the precipitate by centrifugation, washing with deionized water and anhydrous ethanol in sequence, and drying in a vacuum oven to obtain a PBAs precursor.
5. The preparation method according to claim 1, characterized in that: Step 2) The magnetic nanoparticles prepared in the nitrogen-doped carbon are Fe 100-a Co a , Fe 100-b Ni b or Fe 100-c-d Co c Ni d One of the following, where 10≤a<50, 10≤b<50, 10≤c≤30, 10≤d≤20.
6. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment in step 2) is 600-800°C, and the heat treatment time is 2-3 hours; the heat treatment is carried out under a certain atmosphere, and the atmosphere is argon, nitrogen, or a mixed gas of argon and hydrogen, wherein the volume ratio of hydrogen in the mixed gas is 10%.
7. The preparation method according to claim 1, characterized in that: In step 3), the high molecular polymer is one of polyurethane, polyvinyl alcohol, polydimethylsiloxane or polyvinyl butyral; the mass ratio of the magnetic nanoparticles @ nitrogen-doped carbon to the high molecular polymer is (1:9) to (2:3).
8. The preparation method according to claim 1, characterized in that: In step 3), the magnetic nanoparticles @ nitrogen-doped carbon are mixed with a high molecular polymer solution, and the sample is evenly dispersed by ultrasonic treatment, and then quickly poured into a mold. After the mold is filled by mechanical oscillation, it is placed in a vacuum oven for degassing and degassing, and then dried to form a flexible composite sheet.
9. The preparation method according to claim 1, characterized in that: The flexible composite sheet is composed of magnetic nanoparticles@nitrogen-doped carbon / high molecular polymer, and the mass fraction of the magnetic nanoparticles@nitrogen-doped carbon in the flexible composite sheet is 10-40 wt.%.
10. An energy conversion device based on a flexible electromagnetic wave absorbing material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Passive RFID Temperature Tags
CN104899638B
Self-generating passive padlock and charging method thereof
CN109898937A
Wireless switching device and control method thereof
CN113346888A
Sweat PH value passive detection device and method based on flexible digital micro-fluidic chip
CN113866230A
Wireless self-powered humidity sensing system based on friction nanometer generator
CN114965610A